Physical Oceanography of the Dying Aral Sea - Zavialov, Peter O. (Geophysical Sciences,, 2005)
Physical Oceanography of the Dying Aral Sea describes the background, present crisis state, and possible future of this peculiar inland water body from the physical oceanographic standpoint. Based on a wide range of material, a large part of which was published in Russian and has not been previously available to the international reader, the book first provides an historical overview of this unique system, which possesses both lake and sea properties. Next, the current physical state of the lake is described, partly based on original field research and model experiments, along with the remote sensing data, model results and analyses extracted from recent literature. Next, book attempts to forecast the forthcoming state of the Aral Sea and identify plausible future scenarios. Finally, the book discusses the Aral Sea dessication viewd as a part of the global perspective.